Modelling the Influence of Evaporation on Residual Chlorine in Water Storage Tanks Using CFD - Tulirinya, John; Awichi, Richard O.; Kamugisha, Fulgensia M.; Nagulama, Moses (East African Nature and Science Organization, 2021)
Water storage tanks are usually utilized in water distribution systems (WDS) to meet the water demand fluctuations. Chlorine is the most common disinfectant used to disinfect water supplies. However, variations in the rate of chlorine decay in these storage tanks are one of the greatest limiting factors in ensuring adequate water treatment process and giving guarantee to its efficiency. These variations could be due to some inadequately tested mechanisms of chlorine reactions in bulk fluid, chlorine reactions with storage tank walls, and natural evaporation. This study presents Computational Fluid Dynamics (CFD) modelling approach to assess the influence of evaporation on residual chlorine in water storage tanks. Findings indicate that an increase in the evaporation rate accelerates the rate at which residual chlorine is lost. It is concluded that temperature is the main factor influencing evaporation, which in turn causes the disappearance of residual chlorine within the water storage tanks.